Analysis of road accident cases in Petaling Jaya using : geographical information system [GIS] application between year 2014 and 2015 / Nik Lailawati Che Lah - Che Lah, Nik Lailawati (2018)
The road accident is one the major problems experienced by every national. According to specialist research about the road accident like Jacobs and Sayer (1983) already give figure for this problem like the road accident has resulted 300,000 to 400,000 fatal every year and the injury risk and death is highest if compared to other accidents. The aim of this study to determine the relationship of the road accident with the population in Petaling Jaya for year 2014 and 2015. Kernel Density Estimation (KDE) method is use for the hotspot accident cases. A kernel density estimation map was created and subsequently disaggregated by cell density to create a basic spatial unit of an accident hotspot. The study also determine the relationship between population with accident cases. Therefore, the benefit of this study is to approach implemented in the ESRI ArcGIS environment.